Onconephrology: The time has come - Kolesnyk, M. (Ukrainian Journal of Nephrology and Dialysis, 2023)
Why did this time come and how this direction (subspecialty) onconephrology formed? The effect of actual renal cancer (RC) or malignant lesions of extrarenal localization on the condition of the kidney is realized in different ways. Renal cancer can occur in a healthy kidney or a patient with CKD of any stage, moreover, the higher the stage, the higher the risk of renal cell carcinoma (RCC) [1]. It can cause kidney damage due to the formation of almost the entire spectrum of glomerulopathies or A-amyloidosis [2]. 25-30% of patients with RCC before surgery have CKD of various stages [3]. In addition, almost any extrarenal localization of a malignant process can directly or indirectly cause damage to healthy kidneys or worsen the course of pre-existing CKD, and an increase in its stage limits the options for choosing a treatment option [4]. Antitumor therapy, as it has significant nephrotoxic potential, can be another source of various glomerulopathies, acute tubulointerstitial nephritis, acute kidney injury, and increased rate of progression of CKD [5]. In general, it became clear that RC and malignant processes of extrarenal localization can cause a wide range of negative kidney consequences; under both scenarios, treatment results, quality, and life expectancy of cancer patients deteriorate significantly. The issue of starting or stopping the use of dialysis renal replacement therapy methods, kidney transplantation in patients who have survived cancer, and the risks of developing cancer in patients after kidney transplantation and its treatment is difficult to resolve. This is far from the complete list of reasons that encouraged the American Society of Nephrology to hold the first onconephrology forum in 2011, including the first demonstration of the need for the formation of a new component of nephrology, onconephrology. In 2014, the International Community on Cancer and Kidneys (C-KIN) was established, and in 2015, the European Organization for Research and Treatment of Cancer (EORTC) was founded. In 2017, C-KIN launched the Journal of Onconephrology (JON). In 2019, for the first time in Ukraine, at the national oncourology conference, the report "Onconephrology: the time has come" was published, which caused a lively discussion. Since that time, at all nephrology events of the Ukrainian National Academy of Sciences and the National Academy of Medical Sciences, the onconephrology topics were discussed. In 2022, the "Onconephrology" module was included in the specialization program in nephrology, which is carried out at the State "Institute of Nephrology of NAMA of Ukraine" (order of the Ministry of Education and Culture No. 159-d of 06.09.2021). Therefore, solving the majority of the components of the problem of the combination of oncopathology and kidney damage requires either the participation of a multidisciplinary team (oncologist, nephrologist, intensivist, urologist, hematologist, etc.), or a specialist who possesses the listed knowledge and skills in the necessary volumes, i.e. onconephrologist.